2013
DOI: 10.1051/0004-6361/201322053
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Laue lens relying on hybrid quasi-mosaic curved crystals

Abstract: A promising method of concentrating X-and soft γ-rays from celestial sources is a Laue lens. A new scheme for this lens, relying on diffraction in curved Si and Ge crystals, is introduced here. The proposed Laue lens is based on high-efficiency diffraction of curved (111) or (224) crystalline planes, which are bent through quasi-mosaic effect. While diffraction in curved (111) quasi-mosaic crystals is well known and has recently been proposed for a Laue lens, diffraction by quasi-mosaic (224) planes is suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Due to the wealth of diffracting planes with different d-spacing, a large Laue lens was simulated through the LaueGen code. In fact, it has been demonstrated that (311) QM crystals can be profitably used to improve the performance of a Laue lens solely relying on (111) and (422) QM crystals [14]. However, some improvements still have to be accomplished, in order to increase the effective area without increasing the diameter of the lens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the wealth of diffracting planes with different d-spacing, a large Laue lens was simulated through the LaueGen code. In fact, it has been demonstrated that (311) QM crystals can be profitably used to improve the performance of a Laue lens solely relying on (111) and (422) QM crystals [14]. However, some improvements still have to be accomplished, in order to increase the effective area without increasing the diameter of the lens.…”
Section: Discussionmentioning
confidence: 99%
“…Diffraction with curved QM samples has previously been tested exploiting (111) and (422) QM planes, in [13] and [14] respectively. Another set of crystallographic planes that could be used for high-efficiency diffraction are the (311), which can be bent through the QM effect, as shown in Fig 1. In this case, the ratio between the QM and the primary radius of curvature is equal to R QM /R p = 3.455, as can be calculated through the linear theory of elasticity for anisotropic media, following the same procedure explained in [14].…”
Section: Curved Quasi-mosaic Crystalsmentioning
confidence: 99%
See 3 more Smart Citations